Effect of thermal stratification on free convection in a square porous cavity filled with a nanofluid using Tiwari and Das' nanofluid model; Physica E: Low-dimensional Systems and Nanostructures; Vol. 69 - Sheremet M. A. Mikhail Aleksandrovich (2015, 2015)
Title screen